(untitled) - Natan B VargaftiK...[et al.] (Boca Raton, Florida, 1993)
This book covers practically all the available data on the thermal conductivity of pure liquids and gases. It includes new tabulations of thermal conductivity data on the alkali metals both in liquid and gaseous state and, those of the high-molecular organic fluids as well
Keywords: fluids - thermal properties - handbooks, manuals, etc,gases - thermal properties - handbooks, manuals, etc,heat - conduction - handbooks, manuals, etc